Is Smart Beta Strategy a Successful Guide for Creation of Superior Portfolios? - Varghese, P. A.; Anthony, Rintu (Indian Journal of Research in Capital Markets, 2016)
Every investor wants to invest in a portfolio which gives him/her the maximum returns. Building such efficient portfolios has been discussed since time immemorial. This paper described a new strategy called as smart beta which reveals a new and smart set of rules to create efficient portfolios. The main objective of this smart beta is to design a portfolio which manages the risk more effectively than a Cap - Weighted index, and provides a better performance. This paper outlined the limitations of traditional indexing and focused on the prospect of smart beta as a successor to traditional indexing.